Performance-based Assessment for Assessing Science Learning - DOGRA, BHARTI (THE PRIMARY TEACHER, 2015)
There has been a major shift in the area of assessment from ‘outcome based assessment’ to ‘assessment for learning’. The purpose of assessment now is to obtain feedback in order to improve learning of students. The traditional outcome oriented methods of assessments through multiple choice questions, short answer questions or true/false items do not provide any clue about the ability of students to solve real life problems by applying theoretical knowledge gained in the classroom situations. Performance-based assessment tasks provide opportunities to students to demonstrate their problem solving abilities by working individually or in groups. The aim of performance-based assessment is to integrate it with learning. During performance-based assessment, students get opportunities to apply various science process skills such as classifying, formulating hypotheses, interpreting data, and conducting an experiment. Another important highlight of the performance-based assessment is the process through which students go through while engaged in a task along with the product.